Atrial overexpression of angiotensin-converting enzyme 2 improves the canine rapid atrial pacing-induced structural and electrical remodeling: Fan, ACE2 improves atrial substrate remodeling - Fan, Jinqi (Basic Res Cardiol, 2015)
The purpose of this study was to investigate whether atrial overexpression of angiotensin-converting enzyme 2 (ACE2) by homogeneous transmural atrial gene transfer can reverse atrial remodeling and its mechanisms in a canine atrial-pacing model. Twenty-eight mongrel dogs were randomly divided into four groups: Sham-operated, AF-control, gene therapy with adenovirus-enhanced green fluorescent protein (Ad-EGFP) and gene therapy with Ad-ACE2 (Ad-ACE2) (n = 7 per subgroup). AF was induced in all dogs except the Sham-operated group by rapid atrial pacing at 450 beats/min for 2 weeks. Ad-EGFP and Ad-ACE2 group then received epicardial gene painting. Three weeks after gene transfer, all animals except the Sham group underwent rapid atrial pacing for another 3 weeks and then invasive electrophysiological, histological and molecular studies. The Ad-ACE2 group showed an increased ACE2 and Angiotensin-(1–7) expression, and decreased Angiotensin II expression in comparison with Ad-EGFP and AF-control group. ACE2 overexpression attenuated rapid atrial pacing-induced increase in activated extracellular signal-regulated kinases and mitogen-activated protein kinases (MAPKs) levels, and decrease in MAPK phosphatase 1(MKP-1) level, resulting in attenuation of atrial fibrosis collagen protein markers and transforming growth factor-β1. Additionally, ACE2 overexpression also modulated the tachypacing-induced up-regulation of connexin 40, down-regulation of connexin 43 and Kv4.2, and significantly decreased the inducibility and duration of AF. ACE2 overexpression could shift the renin–angiotensin system balance towards the protective axis, attenuate cardiac fibrosis remodeling associated with up-regulation of MKP-1 and reduction of MAPKs activities, modulate tachypacing-induced ion channels and connexin remodeling, and subsequently reduce the inducibility and duration of AF. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00395-015-0499-0) contains supplementary material, which is available to authorized users.